Disguising letters: how children enter the written world - Masdevall Teixido, Sandra; Masgrau Juanola, Mariona (Pulso. Revista de educación, 2011)
In this article we describe an experience based on cross-age collaborative and cooperative learning, in which second-year primary school students act as teachers and tutors of P-5 students and they introduce them in the use of cursive writing. This process is not anymore mechanic and it becomes a chance to develop the basic competences, above all artistic and linguistic. It is a project that promotes primary students artistic and literary creation and formal oral expression and childhood students oral comprehension and writing, in a global and interactive way, where interaction between arts and dialogue between students from different years is the key.
Keywords: Collaborative and Cooperative Learning; Artistic and Literary creativity; Cursive Writing; Cross-age Projects; Oral Comprehension and Expression in Formal Situations